Response‐adapted therapy for aggressive non‐Hodgkin's lymphomas based on early [18F] FDG‐PET scanning: ECOG‐ACRIN Cancer Research Group study (E3404). (30th March 2015) - Swinnen, Lode J.; Li, Hailun; Quon, Andrew; Gascoyne, Randy; Hong, Fangxin; Ranheim, Erik A.; Habermann, Thomas M.; Kahl, Brad S.; Horning, Sandra J.; Advani, Ranjana H.
Summary A persistently positive positron emission tomography (PET) scan during therapy for diffuse large B‐cell lymphoma (DLBCL) is predictive of treatment failure. A response‐adapted strategy consisting of an early treatment change to four cycles of R‐ICE (rituximab, ifosfamide, carboplatin, etoposide) was studied in the Eastern Cooperative Oncology Group E3404 trial. Previously untreated patients with DLBCL stage III, IV, or bulky II, were eligible. PET scan was performed after three cycles of R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) and scored as positive or negative by central review during the fourth cycle. PET‐positive patients received four cycles of R‐ICE, PET‐negative patients received two more cycles of R‐CHOP. A ≥45% 2‐year progression‐free survival (PFS) for mid‐treatment PET‐positive patients was viewed as promising. Of 74 patients, 16% were PET positive, 79% negative. The PET positivity rate was much lower than the 33% expected. Two‐year PFS was 70%; 42% [90% confidence interval (CI), 19–63%] for PET‐positives and 76% (90% CI 65–84%) for PET‐negatives. Three‐year overall survival (OS) was 69% (90% CI 43–85%) and 93% (90% CI 86–97%) for PET‐positive and ‐negative cases, respectively. The 2‐year PFS for mid‐treatment PET‐positive patients intensified to R‐ICE was 42%, with a wide confidence interval due to the low proportion of positive mid‐treatment PET scans. Treatment modification based on early PET scanning should remain confined to clinical trials.